Managing dynamic and adaptive characteristics in software project management - A. Jabar, Marzanah; Mohd Ali, Norhayati; Jusoh, Yusmadi Yah; Abdullah, Salfarina; Mohanarajah, S. (Database Technologies and Applications Research Group (DbTA), Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2019)
There has been a growing interest in the usage and adaptive ramifications within the broad spectrum of agile methodologies and its current trend as an alternative to traditional methodologies has not been widely accepted. Whilst a lot of hype has been seen since its introduction in 2001 with the Agile manifesto where delivery success was promised, software practitioners still appear to be weary as unfavorable usage perceptions dominate the software industry and the transition appears to be a formidable task. Project success and failure scenarios have been researched but the factors that establish these are still widely inconclusive and elusive creating more interest and emphasis for embarking on further research. This paper highlights and investigates the relationship between agile software development methodologies and the success and failure scenarios prevalent in the software industry.